A new record of Badhamia versicolor Lister (Physaraceae) in Poland - Pliszko, Artur; Bochynek, Anna (Biodiversity: Research and Conservation, 2017)
The paper presents a new Polish record of Badhamia versicolor, a nationally rare and red-listed species of Myxomycetes. It was discovered on the edge of the disused sand and gravel pit (formerly, a gravel mine of the Polish State Railway) in the town of Suwałki, north-eastern Poland. Two small clusters of mature fruiting bodies of B. versicolor were noticed on a bark of living poplar (unidentified species of Populus) and on a fallen leaf of the same poplar tree. Photographic documentation of specimens collected from a new locality is provided.